A Escola Normal do Amazonas e o desenvolvimento de Manaus na passagem do século XIX para o século XX - Alexandre, Maria de Oliveira (Brasil, 2024)
The present work aims to analyze the history of the creation of the Normal School of Amazonas (currently Institute of Education of Amazonas) and its relationship with the growth of the city of Manaus at the end of the 19th century and the beginning of the 20th century, a period known as the Amazonian Belle Époque. Situated in the field of the history of education, this study stems from a notable scarcity of research directed at the theme of teacher training at the secondary level in the State of Amazonas. Based on this observation, and being more specific, we determined our chronological focus at the beginning of the 1880s, with the foundation of the school and its effects on the local society, concluding our studies within the rubber economic cycle, in the 1920s. Our main object, therefore, is to study the importance of the establishment of the Normal School of Amazonas for the region’s development. As specific objectives, we seek to understand the context in which the Normal School emerged in Amazonas, analyze the structure and functioning of the unit, and finally, relate the creation of the Normal School of Amazonas to the development of the city of Manaus. For this, we will take as categories of analysis Memory (Motta, 1998; Le Goff, 1990), Educational Institutions (Noronha, 2007; Sanfelice, 2007), and the Curriculum (Goodson, 1997), based on the methodology of documentary research (Godoy, 1995; Furtado, 2011).